OVERVIEW OF THE MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN MERPATI IN VILLAGE JANGANJANGAN PUJANANTING SUB-DISTRICT, BARRU DISTRICT - Lubis, Iksan Adiputra Lubis; A.Ariyadi; Muliati (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal